Development and evaluation of BaFe12 O19-PANI-MWCNT composite for electromagnetic interference (EMI) shielding - Zahari, M.H.B. (Electromagnetics Academy, 2018)
The salient individual properties of BaFe12 O19, MWCNT, and PANI show promise in exhibiting excellent electromagnetic interference (EMI) shielding when they are combined. This research work focuses on developing a composite consisting of all three materials through a simple polymerization process and then evaluating its potential EMI shielding behaviour through electromagnetic measurements. The composite formation was morphologically and structurally verified through XRD, FTIR and FESEM measurements. The presence of main functional groups characteristic to PANI in the composite samples as shown by its FTIR spectra indicates its successful preparation through this method while FESEM micrographs show the random distribution of the composite constituents. The composite is conductive in nature with values reaching as high as 12.43 S/m for the composite with the highest MWCNT wt (BPM 1 3 25). Electromagnetic measurements done at the X-band show promising EMI shielding behaviour in all prepared composites. The overall highest SEA values are shown by sample BPM 1 3 25 with a minimum shielding value of 65 dB throughout the whole frequency band, far exceeding that of pure MWCNT. Â© 2018, Electromagnetics Academy. All rights reserved.